Design and and creation of a gender literacy program for the Center for Women's Studies Library of the University of the Philippines - Montes, Merselle F. (2015)
This is a study focused on the creation and design of a library-based gender literacy program based in the University of the Philippines Center for Women's Studies Library. The study sought to discover the different considerations in creating the program in the said institution. The study also sought to discover what the students wanted to know about gender issues, their preferred media for learning, and their potential responsiveness to such a program. The study narrowed down the vast pool of knowledge on gender issues into the essential topics needed by the University's students and create modules that would equip them with the information they need and want to know. The study was qualitative in nature, with the goal of discovering the in-depth ideas and views of its participants. The study had various phases of data gathering. The views of the Institution were determined through interviews and constant consultation throughout the course of the research, while the views of the students were collected through focus group discussions. Consultations with the UP Diliman Gender Office were also done by the researcher.